A quantitative analysis of the biological pump in the oligotrophic subtropical North Atlantic - Dietze, Heiner (2004)
The oceans are by far the largest global reservoir of carbon that is available on shorter than geological timescales. Its stock exceeds by more than 50 times the atmospheric inventory of carbon dioxide, a key "greenhouse" gas. Thus it is evident that the understanding of global climate change must be accompanied with a quantitative understanding of mechanisms governing the carbon inventory of the oceans. The aim of this thesis is to improve our understanding of these mechanisms in the North Atlantic Ocean. The focus is on the oligotrophic subtropical gyre, where the magnitude and even the direction of its biotic contribution to the air-sea flux of carbon dioxide is subject to a controversy. This controversy is based on an inconsistency between estimates of biotically-effected carbon export inferred from oxygen utilisation rates in the thermocline and local measurements of turbulent nitrate supply to the surface layer. Observational data and results from an eddy-permitting biogeochemical ocean model presented here, indicate that the mismatch between nitrate supply to the surface layer and oxygen utilisation at depth is reduced by 20% if physical processes previously neglected are accounted for. The remaining 80% are ascribed to biogeochemical processes, namely nitrogen fixation and subduction of dissolved organic carbon. In addition a caveat concerning a standard method used to distinguish between physically and biotically effected air-sea oxygen fluxes is reported.